Parâmetros de qualidade de ensino superior: análise institucional em IES privadas do estado de São Paulo - Crubellate, João Marcelo (2004)
The aim of this research was to study the institutionalization of legally prescribed Brazilian higher education criteria of quality among higher education organizations (IES) in São Paulo State, considering the relations among institutional-environmental patterns, interpretive patterns and the strategic responses of those IES. The method that characterizes this research is the comparative study of cases, with the use of multiple sources of evidences. Data were collected by consulting the Brazilian higher education law, publications managed by those IES, questionnaire and semi-structured interviews. The questionnaire was sent to private IES located in the São Paulo State and allowed to classify 44 IES (those that answered the questionnaire) in 3 groups (further grouped again in only 2 groups), according to strategic responses declared for IES main director to legally prescribed higher education criteria of quality (questionnaires were analysed by statistic procedures). Among those 44 IES, 9 cases was deliberately selected and studied by qualitative research procedures, including document analyses, qualitative content analyses and cognitive maps. Results validate most hypotheses formulated in the study, corroborating the relations among institutional patterns, interpretive and cognitive patterns and strategic responses. In those IES were strategic response was identified as Partial Acceptance of higher education criteria of quality, criteria were mainly interpreted by directors as source of efficiency, that is, as enough to offer higher education of high quality (and, secondary, as source of legitimacy). Moreover, in these cases directors put focus specially on normative and cognitive elements of the institutional environment to explain organization actions in attending education law. In those IES were strategic response was identified as Partial Rejection of higher education criteria of quality, criteria were strongly interpreted by directors as source of legitimacy, that is, as a way to improve organization image before market and Brazilian Ministry of Education. In these cases criteria was explained as necessary to avoid legal sanction and directors put focus mainly on legalregulative and normative elements of the institutional environment to explain organization actions in attending education law. Differences were identified in the environment characteristics according to those IES directors definition, too. It was possible to suggest that results point to two different vias of institutionalization of those criteria. One of them is related to the first group of IES, organizations that accept as been real the symbolic relation between legal criteria of quality and high education quality. Another is related to the second group of IES, organizations that do not accept that relation and obey law only or specially to avoid legal and legitimacy problems. It is believed that those different vias can be explained by the concept of symbolic coupling: in symbolic coupling level, first group of IES shows high level of coupling (that is, tight coupling to symbolic relation legally proposed), but second group do not shows that (then, symbolic decoupling). In this second group was not possible to identify, in general, coupling between the meaning proposed by the law for criteria and the meaning (of those criteria) found in the organizations. Consequences of those conclusions for organizational institutional theory and for Brazilian higher education system are, finally, discussed.